Restrained rehabilitation: an approach to children and adolescents with unexplained signs and symptoms. Issue 5 (1st May 2003) - Calvert, P; Jureidini, J
Abstract : The validation of treatment approaches for children and adolescents diagnosed with unexplained signs and symptoms is made difficult by the variety of clinical presentations and the different developmental levels of different patients. There is little evidence about what combination of approaches is most successful. This article uses what evidence is available to develop a coordinated multidisciplinary rehabilitation package that ensures consistency and can be evaluated. The package is organised around a psychologically informed physical rehabilitation programme. The need for coordination and a common approach between medical, allied health and psychological staff, and family is formally addressed. The approach is illustrated with a case study.